Medical Considerations for Exercise in Older Adults. Issue 1 (January 2016) - MacArthur, Peter H.; Umarvadia, Jitesh; Howard, Thomas M.
Abstract : Exercise training has many known benefits in the older adult population including prevention and treatment of chronic disease, reducing the risk of falls, improving cognitive function, and increasing self-esteem. When evaluating and prescribing an exercise program in the older athlete, medical history, medications, and functional capacity are some of the key factors to consider. We aim to address several of the chronic medical conditions commonly affecting these individuals and their potential effects on exercise training. Furthermore, we provide an overview of preparticipation screening and formulating an exercise prescription, both vital to ensuring safe participation in this age group.